The Effect of Seal Bag Storage towards Dimensional Stability of Alginate Impression Material - Octarina Octarina; Jesslyn Raharja (Faculty of Dentistry, Universitas Trisakti, 2018)
Background: The dimensional stability of alginate impression material is very important for obtaining an accurate cast. Seal bag storage is one way to maintain dimensional stability of the impression material. Objectives: This research aims to compare the dimensional stability of alginate impressions between imprESSIX Color Change (Alginate A), Algeniux Normal Set Major (Alginate B), and Aroma Fine Plus Normal Set (Alginate C). The alginate impressions were stored in seal bags for 0 min, 10 min, 3h, 24h, 72h, 120h, and 168h. Method: Sixty-three gypsum cast samples were obtained from a master die using 3 different alginate impression materials. The alginate impressions were stored in separate seal bags for each of the seven different time intervals, then the samples were poured with gypsum type III. The buccal cusp length from right first molar to left first molar was measured for each gypsum cast sample using calipers and compared with the master die. The data were analyzed with two-way ANOVA followed by post hoc LSD test. Results: The distance between the mesial buccal cusps of the right and left first molar was 52.280 mm for the master die. Gypsum cast samples of alginate A and B showed shorter lengths compared to master die, but the difference was not significant (p>0.05). A significant difference in dimensional stability was observed for alginate C (p<0.05) after 120h (52.080 mm) and 168h (52.057 mm). Conclusion: Dimensional stability of alginate impression was influenced by alginate composition and seal bag storage time. Seal bag storage could hold the dimensional stability of alginate A and B up to 168h, but for alginate C, the stability only lasted for 72h.